فعالية استخدام رسيت ستون (Rosetta stone v.3.4.7) لترقية مهارة الاستماع - Jannah, Ida Mifatkhul; Junaedi; Rondi, Muhammad; Fitri, Lailatul; Khusnia, Maslachatul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Maharah istima' is one of the four maharah languages. Maharah istima' aims to train basic human abilities in listening to languages, especially Arabic. Listening is a basic human ability which is possessed from the beginning of his birth until throughout his life. However, at the level of language learning there is a low level of student interest in learning specifically. This problem makes researchers want to know the effectiveness of using Rosetta Stone v.3.4.7 which is a learning method that is able to provide solutions for students to increase interest in listening lessons in particular. As for the importance of teaching aids, because they have the most influence on the senses and to ensure understanding, they do not see as the person who hears. Teaching aids bring joy to students, renew their activities, help build facts in students' minds, and bring lessons to life. Teaching listening skill - like other teaching - requires steps and stages. But above all, several foundations should be taken into account in teaching listening to be effective teaching, namely: 1. Elaborate the material that the students will listen to in a manner that suits their abilities, 2. Raise students motives for listening, which requires a temporary response, and critical listening. The result of this research is a special learning process using  Rosetta Stone v.3.4.7  method and the obstacles found in using the Rosetta Stone v.3.4.7   method.